Konsep Keadilan Menurut Filsafat Hukum Islam Dalam Perkawinan Poligami - -, Wirdyaningsih (UI Scholars Hub, 2018)
Islamic marriages allow polygamy on the condition that the husband can do justice. This fair concept is interesting to study because it is not easy to measure fairness in an action. By going through juridical analysis studies and using literature research, the authors examine two main issues, namely the philosophy of polygamy marriage according to Islamic law and how the concept of justice in polygamy is applied according to the philosophy of Islamic law. There are several conditions that must be met for men who will do polygamy. One of the requirements mentioned in the Qur'an is that it can be fair. In accordance with the two basic principles of Islamic law, namely justice and benefit, polygamy can be done when the two principles are fulfilled. Polygamy must be in accordance with the two basic principles of Islamic law, namely justice and benefit. Justice that can be measured is qualitative but with regard to benefit. Therefore, husbands and wives who will do polygamy should think about the nature of a polygamous marriage.